Sustainability of beekeeping under rubber plantations in India : The case study of a rubber producers society - Veeraputhran S; Jose V T; Viswanathan P K (International Workshop on Conservation and Management of Bees for Sustainable Development and Honey Festival (Apiexpo-2003), 13-18 October 2003 Bangalore.)
Beekeeping in rubber plantations in India, particularly in Kerala, is a potential source to maximise the net income and employment of natural rubber growers. However, it has not received adequate attention even in the context of market uncertainities in the post-economic reforms phase since 1991-92. Though the initiatives of beekeeping in rubber plantations dates back to the 1920s with institutional intervention through co-operatives, due to inherent limitations of such interventions not only the potential of rubber honey remains to be under-exploited but the income of gwowers cannot be augemented as well. In this context, an attempt is made in this paper to examine the potential, the trends in the commercial exploitations of rubber honey and the factors constraining the popularisation of beekeeping by these co-operatives in the backdrop of the achievements made by small voluntary organisations the Elavampadam Rubber producers Society (ERPS), located in north Kerala, with growers participation in the popularisation of beekeeping and the enhancement of net income of rubber growers. It is observed that, though Kerala constitutes 84 per cent of the total area under natural rubber in India, with the production potential of an average of 52000 MT of honey during the period 1994-95 to 2002-03, only less than three percent of the potential could be commercially exploited so far. The major factors constraining the commercial exploitations are the lack of appropriate extension work, structural characteristics of rubber honey market and the inherent limitations like conventional method of processing, lack of working capital and administrative rigidities associated with co-operatives. Given this background, the role being played by the ERPS in maximising the income of rubber growers through beekeeping substantiates the relevance of RPSS as alternative institutions for the sustainable development of beekeeping through economisation with diversified marketing approaches. The crux of the success story has been the unique marketing strategy of the ERPS in acquiring maximum share in retail prices of honey. Though there are regional variations, other RPS can also attempt to promote and popularise beekeeping in rubber plantations with necessary modifications to suit the local conditions.
Keywords: Beekeeping; India; Rubber plantation